We free the stars - Faizal, Hafsah (Macmillan Children's Books, an imprint of Pan Macmillan, 2021)
The follow-up to the New York Times bestselling novel We Hunt the Flame! After the battle on Sharr that closed We Hunt the Flame, Zafira and Nasir return to a ghostly Sultan's Keep, low on resources and allies alike. The dark forest has fallen, but the kingdom teems with fear of the Lion of the Night's return. As Nasir fights to command the dark power in his blood, Zafira fights against a very different darkness festering through her bond with the Jawarat. The second book in the Sands of Arawiya duology, by the masterful Hafsah Faizal